2016
DOI: 10.1038/srep36634
|View full text |Cite
|
Sign up to set email alerts
|

Distinct role of IL-1β in instigating disease in Sharpincpdm mice

Abstract: Mice deficient in SHARPIN (Sharpincpdm mice), a member of linear ubiquitin chain assembly complex (LUBAC), develop severe dermatitis associated with systemic inflammation. Previous studies have demonstrated that components of the TNF-signaling pathway, NLRP3 inflammasome and IL-1R signaling are required to provoke skin inflammation in Sharpincpdm mice. However, whether IL-1α or IL-1β, both of which signals through IL-1R, instigates skin inflammation and systemic disease is not known. Here, we have performed ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 36 publications
2
31
0
Order By: Relevance
“…[108][109][110] However, the deletion of IL-1β, IL-1R, NLRP3, or caspase-1 significantly delays dermatitis in Sharpin cpdm mice. 109,111 In line with these findings, IL-1R signaling also upregulates the production of TNF. 112 These studies show that concerted production of IL-1β and TNF can form an inflammatory loop, which is capable of causing destructive autoinflammation, unless curtailed by negative regulators like IL-10.…”
Section: Il-1α and Autoinflammatory Disorderssupporting
confidence: 64%
See 1 more Smart Citation
“…[108][109][110] However, the deletion of IL-1β, IL-1R, NLRP3, or caspase-1 significantly delays dermatitis in Sharpin cpdm mice. 109,111 In line with these findings, IL-1R signaling also upregulates the production of TNF. 112 These studies show that concerted production of IL-1β and TNF can form an inflammatory loop, which is capable of causing destructive autoinflammation, unless curtailed by negative regulators like IL-10.…”
Section: Il-1α and Autoinflammatory Disorderssupporting
confidence: 64%
“…Autoinflammatory dermatitis in Sharpin cpdm mice is completely rescued by genetic deletion of TNF, TNFR1 or downstream signaling molecules . However, the deletion of IL‐1β, IL‐1R, NLRP3, or caspase‐1 significantly delays dermatitis in Sharpin cpdm mice . In line with these findings, IL‐1R signaling also upregulates the production of TNF .…”
Section: Il‐1α and Autoinflammatory Disorderssupporting
confidence: 52%
“…This also suggests that pyrin inflammasome-mediated IL-1β promotes TNF production to modulate certain features of FMF pathology (Supplemental Figure 6). The intersection of TNF with IL-1 cytokines has also been observed in other autoinflammatory models, including neutrophilic dermatosis (56) and skin inflammation (57)(58)(59). A recent study reported that TNF promotes expression of inflammasome components and inflammatory disease in a mouse model of NLRP3 inflammasomopathy (60,61).…”
Section: Discussionmentioning
confidence: 82%
“…These mice are runted and develop spontaneous systemic inflammation with apparent inflammation of the skin as early as 3–4 weeks after birth . Nlrp3 , Caspase1 , Caspase11 , Il1r , and Il1b deficiency all delay the onset of dermatitis in Sharpin cpdm mice . Sharpin cpdm inflammasome component–deficient mice still develop a full spectrum of disease, suggesting that the IL‐1 signaling pathway may play only a minor role in disease progression.…”
Section: Il‐1‐related But Inflammasome‐independent Autoinflammatory Dmentioning
confidence: 97%
“…138 Nlrp3, Caspase1, Caspase11, Il1r, and Il1b deficiency all delay the onset of dermatitis in Sharpin cpdm mice. 139,140 Sharpin cpdm inflammasome component-deficient mice still develop a full spectrum of disease, suggesting that the IL-1 signaling pathway may play only a minor role in disease progression. Another recent study has determined important roles for RIPK1, TNF, and myeloid differentiation primary response protein 88 (MyD88) signaling in the complete rescue of skin inflammation in Sharpin cpdm mice.…”
Section: Il-1-related But Inflammasome-independent Autoinflammatory Dmentioning
confidence: 99%